Mediating Effect of Metabolic Diseases on the Relationship Between Dietary Inflammatory Index (DII) and Cataract Prevalence: A Structural Equation Modeling Study - Eunji Lee; Woori Na; Cheongmin Sohn (Applied Sciences)
Background/Objectives: Aging increases the risk of metabolic diseases, such as diabetes, hypertension, dyslipidemia, and obesity, which may contribute to cataract development. This study examined whether metabolic diseases mediate the relationship between the dietary inflammatory index (DII) and cataract prevalence using structural equation modeling (SEM). Methods: Data were obtained from 9260 individuals aged 40 and older who participated in the 8th Korea National Health and Nutrition Examination Survey (KNHANES 2019–2021). DII scores, calculated from 24 h dietary recall, reflect the inflammatory potential of the diet, with higher scores indicating a more pro-inflammatory profile. SEM was applied to assess mediation effects, and analyses were conducted using SPSS 29.0 and AMOS 29.0. Results: Among the participants, 1853 individuals (20.0%) were diagnosed with cataracts, and the mean DII was 1.5 ± 2.8. In the high DII group, the risk of hypertension (β = 0.077, p < 0.001) and dyslipidemia (β = 0.033, p = 0.001) increased significantly. Hypertension (β = 0.187, p < 0.05), diabetes mellitus (β = 0.132, p < 0.05), dyslipidemia (β = 0.108, p < 0.05), and obesity (β = 0.025, p < 0.05) had direct effects on cataract prevalence. Diabetes 0.002 (p < 0.05), hypertension 0.014 (p < 0.05), and dyslipidemia 0.004 (p < 0.05) also showed significant indirect effects. Conclusions: Metabolic diseases mediate the relationship between DII and cataracts. Managing inflammation and metabolic health may reduce cataract risk.